Peningkatan Hasil Belajar Matematika Tentang Pecahan Melalui Model Interaktif pada Siswa SD - Rokhaniyah Rokhaniyah (Academy of Education Journal, 2018)
This study aims to determine the problems that occur in learning mathematics about fractions and find ways to solve these problems. The focus of the problem under study is "How to improve Mathematics Learning Outcomes of Fractions of Class V Students in Tanjung Kulon Elementary School, Jatilawang District, Banyumas Regency". This research was conducted using observations from peers, an indicator of increased learning outcomes with quantitative data. As the subject of the study was the fifth grade of SD Tunjung Kulon Elementary School. With a total of 20 students, the time for implementing the action consists of three cycles per cycle. Using the Interactive Learning Model. The results showed an increase in learning outcomes, the initial condition of the completeness level was only 20% after the improvement was made to be 85%, it could be stated that the improvement was successful.